Knockdown of NDRG1 promote epithelial–mesenchymal transition of colorectal cancer via NF‐κB signaling. Issue 4 (23rd June 2016) - Ma, Junli; Gao, Quanli; Zeng, Shan; Shen, Hong
Abstract : Background: NDRG1 plays important roles in tumor growth and metastasis of colorectal cancer (CRC). The relation between NDRG1 and metastatic colorectal cancer (mCRC) has not been identified and the mechanism of NDRG1 involving in mCRC needs to be elucidated. Methods: Correlations between NDRG1 and clinicopathological characteristics and prognosis of 164 patients with mCRC were evaluated. Sensitivity of NDRG1‐knockdown colon cancer cell to irinotecan (CPT‐11) was determined by MTT assay. Blocking of NF‐κB signaling by p65 siRNA interference was carried out to explore the mechanism of NDRG1 involving in epithelial–mesenchymal transition (EMT)‐regulated invasion and metastasis of CRC. Results: NDRG1 expression was significantly negatively correlated with differentiation ( P  = 0.008) and lymph node metastasis ( P  = 0.016) of mCRC. NDRG1 was a favorable prognostic factor of mCRC, although might be responsible for CPT‐11 resistance in vitro. Knockdown of NDRG1 promoted EMT of CRC cells via NF‐κB signaling. Depletion of NDRG1 increased phosphorylation level of NF‐κB. E‐cadherin expression was increased and Vimentin expression was reduced in the p65‐siRNA treated group, compared with the control group ( P <  0.001). Conclusions: NDRG1 appears to prevent EMT‐induced metastasis by attenuating NF‐κB signaling in mCRC. NDRG1 may be an independent prognostic factor for good survival of mCRC. J. Surg. Oncol. 2016;114:520–527 . © 2016 Wiley Periodicals, Inc.